Pengaruh Skeptisisme Profesional Auditor, Risiko Audit, Pengalaman Audit, Keahlian, Dan Independensi Terhadap Ketepatan Pemberian Opini Audit: Studi Empiris pada KAP di Jakarta dan Tangerang - Christiani, Agnes Puji; Kurnia, Ratnawati (Ultimaccounting Jurnal Ilmu Akuntansi, 2012)
The purpose of this research is to determine the impact of between the auditor's professional skepticism, audit risk, audit experience, audit expertise, and independence with the accuracy of audit opinion by public accountant. This research done by survey method the responden are senior auditors, supervisors, managers, and partners in public accountant office in Jakarta and Tangerang. The samples were taken by non-probability sampling method with using convenience sampling. The total samples used in analysis are 102 responden. Data analysis conducted by using multiple regression. Hypothesis testing to determine whether any significant relationship between auditor's professional skepticism, audit risk, audit experience, audit expertise, and independence with the accuracy of audit opinion by public accountant. The result of hypothesis testing showed that professional skepticism, auditors, audit risk, the audit experience, expertise, and independence as simultaneously have significant influence to the accuracy of audit opinion by public accountant. Meanwhile, only audit experience and independence has significant influence to the accuracy of audit opinion by public accountant. Other three variables, which auditor's professional skepticism, audit risk, audit expertise have no significant influence to the accuracy of audit opinion by public accountant. Keyword: auditor's professional skepticism, audit risk, audit experience, audit expertise, and independence with the accuracy of audit opinion by public accountant.